Dataset for classifying English words into difficulty levels by undergraduate and postgraduate students - Nisar Ahmad Kangoo; Manmohan Sharma; Apash Roy (Data in Brief, 2023)
The ability of a student to know the meaning of a word depends on the level of education they are at. Since most information is stored in text, students use electronic gadgets to obtain information about their study subjects. This Dataset provides the classification of English words into difficulty levels as viewed by the students at graduation and post-graduation levels. The Dataset in the consideration categorizes the English words into difficulty levels as viewed by undergraduate and postgraduate students in non-native English-speaking countries like India. Some words are neither considered difficult by undergraduate nor postgraduate students. The Dataset can help researchers provide meaning to difficult English words in native languages at runtime (while reading a text document). The Dataset can also help authors write their books and articles for undergraduate and postgraduate levels in different tones, keeping their vocabulary in view.